DAMPAK UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA SEKTOR FORMAL DAN INFORMAL: ANALISIS SPASIAL - Muh. Nuhradi; Diah Widyawati (Jurnal Ekonomi-Qu, 2019)
There is possibility of bias in previous study about impact of minimum wages on labor absorption in formal and informal sectors because it has not yet accommodated the spatial effects of inter-regional labor market dependencies. This study aims to examine impact increasing of minimum wage on labor absorption in formal and informal sector without spatial effects then compared with if there are spatial effects. Without spatial effect, the model used is panel model and with spatial effect, model used is Panel Spatial Auto-Regressive model. The dependent variable used is labor absorption in formal sector relative to informal sector, whereas the independent variable is the real minimum wage in the form of the natural logarithm. The result of both models showed that increasing of minimum wage significantly reduced the labor absorption of formal sector relative to informal sector. Coefficient value of the impact increasing of minimum wage produced by the spatial model is greater than the non-spatial model whereas from the model criteria results show better spatial model, so it can be concluded there is underestimate in the previous study which does not take into account the spatial dependencies of the labor market.